Roles of career maturity mediating the effects of locus of control and socioeconomic status on career readiness - Mar'atus Sholikah; Muhyadi Muhyadi (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study aimed to analyze students' readiness for careers out of their professions by considering the effect of locus of control and socioeconomic status. Career maturity acted as the variable intervening. The quantitative method was chosen to test the hypothesis. A total of 80 students were selected to be respondents based on purposive sampling. Model testing was done by using PLS-SEM. The findings of this study found that the locus of control influenced student career readiness. Conversely, socioeconomic status had no significant effect on their career readiness. On the other hand, this study's career maturity partially mediates between locus of control and career readiness. Regarding the effect of socioeconomic status on career readiness, career maturity in this study was known to have a role as an explanatory or predictor. This study concluded that if students wanted to improve their career readiness, they should pay attention to the locus of control and achieve career success. This study's results contribute to institutions, educators, students, and counselling, informing that individual career maturity is an effective way to facilitate students' readiness in their career decision-making process. Future studies should adopt essential variables related to career readiness that is not examined in this study.